Bhutan's Development Nexus: Economic Analysis of the Complex Interplay between Carbon Neutrality, Gross National Happiness and Economic Growth - Yangka, Dorji (Curtin University, 2019)
This thesis explores if and how Bhutan can maintain its Carbon Neutral pledge, in light of its growing economy and increasing Greenhouse Gas, while continuing its pursuit of its Gross National Happiness (GNH) strategy as part of its development commitments. It investigates the complex interplay between these three core goals and options for their integration, thus establishing a model for how the development nexus can be resolved for emerging economies.